Histopathological correlation of abnormal uterine bleeding in perimenopausal women - Verma, Deepika; Verma, Abhyudaya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal uterine bleeding (AUB) is one of the commonest conditions for which patients seek advice in the gynaecology outpatient department. The objective of this study was to evaluate various histopathological features in endometrial curetting’s of patients above 40 years of age, complaining of abnormal uterine bleeding (AUB) and correlating them with clinical presentations. Methods: A total of 100 endometrial curetting’s were obtained by dilatation and curettage done at the department of gynecology and obstetrics, Mamatha Medical College, Khammam, Telangana, India. Results: Out of 100 cases studied, menorrhagia (57%) was the commonest clinical condition. Hyperplastic (48%) change was the commonest endometrial change, followed by proliferative change (18%). Hyperplasia when further categorized showed simple hyperplasia as the dominant sub-type. Hyperplasia was the dominant change observed in menorrhagia, polymenorrhoea, metrorrhagia, and post-menopausal bleeding. Conclusions: Menorrhagia was the leading cause of AUB. Hyperplastic endometrium was the most common histopathological finding, with simple hyperplasia being commonest sub-type. Hyperplasia is also commonest endometrial pattern seen in patients with menorrhagia. AUB occurring at perimenopausal age is alarming and needs thorough evaluation, as it could be the only clinical manifestation of endometrial cancer, as was noticed in this study.